Pengembangan Instrumen Evaluasi “Self Evaluation” dan “Peer Evaluation” Layanan Konseling Individual di Sekolah bagi Konselor - Muya Barida; Sutamo Sutamo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Individual counseling services in schools need to gain the attention of policymakers, among others, by the evaluation. The purpose of this research to produce products such as performance of counselors in individual counseling services instrument in schools both self evaluation and peer evaluation. This study uses a Research and Development Model. The steps of this study include: (1) Research and information collecting,(2) Planning, (3) Develop preliminary form of Product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing,(7) Operational product revision, (8) Operational field testing, and (9) Final product revision. The subjects of this research were junior high school counselors in Sukoharjo, junior high school counselor in Bantul and Expert of Guidance and Counseling. Early stages of product development gained 40 grains item instrument, later revised to 60 grains item. Further trials conducted end gained 57 grains of items for self evaluation and 57 grains of items for peer evaluation. The results of tests on a wider field gained 51 grains of items for self evaluation and 50 grains of items for peer evaluation.